Effect Of Water Quality And Marine Phytoplankton Community Structure On Shrimp Production In Tropical Ponds - Zakaria, Mohd Rozhan (2009)

(untitled)
Production of giant black tiger shrimp (Penaeus monodon) in earthen ponds in the tropical region may vary as the pond matures, depending on water quality and phytoplankton community structure. The objectives of the present study were to determine water quality and marine phytoplankton succession in ponds of different ages, to nutritional value of isolated species of a dominant cyanobacterium in the shrimp ponds in comparison with a beneficial diatom and green alga and to investigate how phytoplankton community structure could be affected by alteration of macronutrient concentrations in mixed cultures. The field study was carried out in an intensive shrimp farm in Kuala Selangor, Malaysia. Phytoplankton and water samples were collected from ponds of different ages categorized as new (<1yr), intermediate (2-5yrs) and old (>10yrs), for 16 weeks of shrimp culture. Fluctuation of nutrient and chlorophyll-a concentrations were not different from other tropical shrimp ponds in the region. Cyanobacteria (five genera), diatoms (24 genera), dinoflagellates (four genera) and green algae (three genera) were four dominant groups of phytoplankton found in all the shrimp ponds. Diatoms were dominant during the early stage of the culture in new ponds whilst blue–green algae dominated intermediate and old ponds throughout the culture period. Shrimp production in new ponds were significantly higher than intermediate and old ponds (p<0.05) probably due to the abundance of diatoms at the beginning of the culture cycle, suitable as live feed for zooplankton and shrimp larvae. Pseudanabaena tenuis was found abundant in all pond categories throughout the culture period. The cyanobacterium was isolated for surface structure and proximate analysis in the laboratory. Result showed that P. tenuis have lower nutritional value in comparison with a common diatom (Chaetoceros calcitrans) and a green alga (Chlorella pyrenoidosa), indicating that is was not part of consumable algae among grazers. All the above microalgae species were used in the nutrient enrichment bioassays in the laboratory to determine the growth and competition among species when grown singly and in mixed cultures. The result showed that the diatom grew well in single cultures and competed successfully over other microalgae in mixed cultures when silica concentrations increased whilst other essential growth nutrients were not limited. This present research gives an idea of how shrimp production in ponds of different ages could be affected by water quality and phytoplankton community structure and how alteration of nutrient concentrations could be use to stimulate growth of beneficial algae and suppress harmful algae in mixed culture systems which need further research for better understandings.